Temporary Skeletal Anchorage for camouflaging Class III Malocclusions - Martin Salvador, D; Aznar Arraiz, J; Arias-Camisón, P; Canábez Berthet, A. (Seminars in orthodontics, 2024)
The use of skeletal anchorage for dentoalveolar compensations “camouflaging” in Class III malocclusions in borderline adult patients has become an important treatment alternative. In this article three different types of skeletal anchorage are presented: 1) retromolar miniscrews 2) miniplates with the use of Class III elastics and 3) osseointegrated implants. Furthermore, the three-dimensional nature of class III malocclusions implies that we not only have a sagittal problem but also a transverse and vertical alterations. To resolve transverse discrepancies in many instances we resort to corticotomies to be able to exceed the biological limits.